Metal-organic frameworks for platinum group metal extraction - Trenholme, W.J.F. (2016)
This Thesis describes the synthesis and characterisation of a variety of functionalised metal-organic frameworks (MOFs). These MOFs have been used for the extraction of platinum group metal (PGM) compounds from aqueous and organic solvents and for the storage of gases such as CO2, CH4 and the C2 hydrocarbons. Chapter 1 contains an introduction to PGM properties and uses with specific focus on the chemical properties which allow for separation of PGMs from base metal compounds and for separation between different PGM compounds. The synthesis and structure prediction of MOFs is then introduced, leading into an overview of the use of functionalised MOFs, especially those used for the encapsulation and extraction of metal ions from solution. General experimental techniques and details are described, as is the theory behind inductively coupled plasma optical emission spectrometry (ICP-OES), the most widely used analytical technique reported in this work. Chapter 2 describes the synthesis of chemically stable amine-functionalised Zr(IV) MOFs; UiO-68-NH2 and UiO-66-NH2, for extraction of PGM anions from aqueous and acidic solutions. ICP-OES was used to show that both materials exhibit close to 100% uptake of PtCl62- when present in just 3.5 equivalents per anion, comparable to the best materials reported for PtCl62- extraction. Furthermore, UiO-66-NH2 exhibited consistently higher PtCl62- uptake from aqueous solutions than four industrially used materials supplied by Johnson Matthey. Back-extraction of PtCl62- was demonstrated simply by heating the doped MOF in 4 M HCl, removing 99% of the PGM while maintaining the phase and crystallinity of UiO-66-NH2. Separation of PdCl62- from PtCl62- from acidic HCl solutions was exhibited by UiO-66-NH2, showing an exceptional selectivity of 20:1 for Pd:Pt from 2 M HCl. Likewise, 100% selectivity for PtCl62- and PdCl62- over CuCl2 and CuSO4 from acidic solutions was demonstrated, even in cases in which Cu was in 100-fold excess. Solid state NMR was employed to confirm the interaction between the framework and the PGM anions, with XPS results suggesting that the encapsulated Pt species within UiO-66-NH2 may be PtCl3(NH2)3 or PtCl4(NH2)2. Chapter 3 describes the synthesis and characterisation of a series of functionalised Cu(II) MOFs, NOTT-151, -155, -125 and -150, for the removal of neutral PGM complexes, Pd(OAc)2, PtCl4 and Rh2(OAc)4, from THF. The design of the MOFs allowed for an investigation into the effect of different topologies (ssa and fof), cage sizes and functional groups (amine, oxamide and methyl) on the uptake of each PGM complex. ICP-OES analysis showed that the MOFs were capable of extracting each PGM complex. The oxamide-functionalised NOTT-125 exhibited the most consistent uptake of Pd(OAc)2 with a maximum capacity of 35 mg g-1 (7 NH(CO)2NH groups per PtCl4). The amine-functionalised NOTT-155 showed the highest uptake of PtCl4, with a maximum capacity of 73 mg g-1 (4 NH2 groups per PtCl4). Uptake of Rh2(OAc)4 was generally low, however NOTT-125 showed a maximum extraction of 87 mg g-1 (3 NH(CO)2NH groups per PGM). The larger pore fof MOFs, NOTT-155 and NOTT-125, were more effective for each extraction than the MOFs of ssa topology, NOTT-151 and NOTT-150. However, of the ssa MOFs, amine-functionalised NOTT-151 was shown to give higher uptake of each PGM than the isostructural methyl-functionalised NOTT-150. This demonstrated the importance of incorporating a functional group capable of coordinating to the metal complex. Chapter 4 introduces the use of a nitrogen-rich triazine core in the synthesis of a variety of organic linkers to prepare MOFs for gas storage applications. The preparation of a novel 3,24-connected Cu(II) MOF of rht topology, denoted NOTT-160, is described and the structure characterised using X-ray crystallography. The material is shown to exhibit good uptake of C2 hydrocarbons with uptake of 128 cc g-1, 115 cc g-1, 110 cc g-1 for C2H2, C2H4, C2H6 respectively at 298 K and 1 bar (this becomes 212 cc g-1, 175 cc g-1 and 201 cc g-1 at 273 K and 1 bar). The selectivities of 79:1 and 70:1 calculated using Henry’s law for the separations of C2H2:CH4 and C2H4:CH4 respectively at 298 K are the third and second highest reported values for a MOF under these conditions. Ideal adsorbed solution theory (IAST) was also employed to calculate and predict these selectivities and shows agreement with the results obtained using Henry’s law. In addition, NOTT-160 shows an exceptional volumetric working capacity for CH4 of 221 cm3 cm-3 at 80 bar and 298 K. This is the second highest working capacity reported for a MOF under these conditions, with the excellent performance attributed to the high porosity and comparatively high crystal density of the material. Chapter 5 contains a summary of the work presented in this thesis.